PISA as a legitimacy tool during China's education reform: Case study of Shanghai - Chenjian Zhang; Alexander Akbik (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2012)
In this paper we examine the Chinese domestic discourse centering on Shanghai's participation in the PISA study and interpretations of the 2009 results. The main focus is to examine why local education authority took part in the PISA project and how actors from the education authority use PISA as a tool to legitimize their reform stance. We adopted discourse and rhetorical analysis techniques and analyzed the data collected from newspapers and official documents. The analysis shows that the local education authority and PISA team used PISA as an external assessment tool to legitimate the pre-existing education reform measures, confirm its leadership, and appeal for the collective actions from other social groups in future reform agenda. Different interpretations of the test results by independent educators and overseas professors are demonstrated to contrast officials' framings and shed light on the rationales behind these framings. This study contributes to the theoretical discussion of how local actors use PISA to respond to domestic and international pressures on education reform and at the same time pursue local political interests. – – In diesem Artikel analysieren wir den innerpolitischen Diskurs Chinas über die Teilnahme Shanghais an der PISA-Studie 2009 sowie über die anschließenden Interpretationen bezüglich der Ergebnisse dieser Studie. Hierbei liegt der thematische Schwerpunkt auf der Forschungsfrage, warum die lokale Bildungsbehörde an PISA teilgenommen hat und wie relevante Akteure diese Teilnahme und die Ergebnisse der Studie als Mittel zur Legitimation von Reformen im Bildungssystem genutzt haben. Dabei haben wir auf die Methoden der Diskurs- und Rhetorikanalyse zurückgegriffen und Daten aus Zeitungen sowie offiziellen Dokumenten analysiert. Diese Untersuchung hat aufgezeigt, dass die lokale Bildungsbehörde und das lokale PISA-Team die PISA-Studie als externes Beurteilungswerkzeug genutzt hat um vorhandene Reformen zu legitimieren, die Führungsrolle der lokalen Behörden zu bestätigen und bestimmte kollektive Aktionen von anderen sozialen Gruppierungen für zukünftige Reformen zu fördern. Verschiedene Interpretationen der PISA-Ergebnisse unabhängiger Bildungsexperten, sowie im Ausland ansässige chinesische Professoren zeigen ein gegensätzliches Bild der offiziellen Interpretation und offenbaren die Gründe hinter diesen. Diese Studie trägt zur theoretischen Diskussion über den Nutzen von PISA durch lokale Behörden bei, die auf den innerstaatlichen und internationalen Druck bei Bildungsreformen reagieren und gleichzeitig lokale politische Interessen verfolgen.
Keywords: 300